Analyse Structurale et Thermique du Composé C21H18ONFBr2 - YAHIAOUI Salem (My University, 2014)
The structure of (E)-N-[(E)-3-[(1R, 2R)-2-(3, 4-dibromo-phenyl)-1-fluro-cyclopropyl]- allylidene]-2-θ-tolyl-acetamide (C21H18ONFBr2, Mr = 479.18) has been determined by X-ray single-crystal diffraction and theoretical calculations to establish the configuration, stereochemistry and a stable conformation of the molecule. The compound crystallizes in the monoclinic space group P21/c, a = 28.3452(10), b = 4.9311(10), c = 14.257(2) Å, β = 102.7654(10) °, V = 1943.5(5) Å3 and Z = 4. The structure has been refined to the final R = 0.05 for the observed structure factors with I > 3(I). Theoretical calculations in the ground state have been carried out for the compound studied using the Hartree-Fock (HF) and density functional theory (DFT) (B3LYP) with 6-31G (d,p) basis sets. The results show that the studied compound prefers the keto form. The compound involves intra- and intermolecular hydrogen bonding of C–HO and C–HF types, which further stabilize the structure and display a trans configuration for the C=N and C=C double bonds. A thermal analysis was performed to verify the stability of the structure and to ensure the quality of the recorded data.
Keywords: X-ray diffraction, crystal structure, insecticide.